PROSPECTS FOR PRESCHOOL EDUCATION IN UZBEKISTAN (Multidisciplinary Journal of Science and Technology, 2025)
This article explores the current state and future prospects of preschool education in Uzbekistan. As a country undergoing major educational reforms, Uzbekistan has recognized early childhood development as a strategic priority for improving human capital and ensuring long-term socio-economic growth. The article examines the recent policy initiatives, institutional reforms, and international collaborations aimed at expanding preschool coverage, improving quality, and ensuring inclusivity. It also highlights challenges such as uneven access, lack of qualified staff, and the need for innovative teaching methods.